Analisis Faktor Risiko Persalinan dengan Tindakan di Lebak Banten - Pristya, Terry Y.R.; Nurcandra, Fajaria; Fitri, Azizah Musliha (Jurnal Kesehatan, 2022)
The maternal mortality rate (MMR) increased from 2007 to 2012. However, based on the 2015 Inter-Censal Population Survey (SUPAS) was decreased. The causes include pregnancy, delivery, and puerperal. The purpose of this study was to analyze delivery risk factors in Lebak Banten in 2019. The cross-sectional study design and data collection were carried out using a questionnaire by interview. The research sample consisted of 120 women of childbearing age who had given birth in Sangiangtanjung Village, Kalanganyar District, Lebak Regency, Banten, and were selected by purposive sampling technique. The variables consisted of delivery methods and 11 independent variables including age, education, occupation, socio-economic, infectious diseases, chronic diseases, hypertension, the danger of pregnancy, the danger of delivery, premature rupture of membranes, and fetal location which were analyzed using multiple logistic regression to determine which variable is most at risk for delivery. It was found that most mothers gave birth normally (90.8%). The remainder performed delivery with measures consisting of vacuum (0.8%) and cesarean delivery (8.4%). The results also showed that women who suffer from hypertension will give birth 7 times greater (95% CI 1.2-39.6) than mothers who do not have hypertension after being controlled by maternal education, chronic disease, and fetal location. There were only one of eleven factors was hypertension which is a risk factor for operative delivery in Lebak Banten. Therefore, it is necessary to promote health to pregnant women to prevent the occurrence of hypertension by health workers to reduce the impact.